Environmental Impact Analysis of Portland Cement (CEM1) Using the Midpoint Method - Oluwafemi E. Ige; Oludolapo A. Olanrewaju; Kevin J. Duffy; Obiora C. Collins (Energies, 2022)
The cement industry confronts significant challenges in raw materials, energy demands, and CO2 emissions reduction, which are global and local environmental concerns. Life cycle assessment (LCA) has been used in many studies to assess the environmental impact of cement production and investigate ways to improve environmental performance. This study aims to analyse the environmental impact of Portland cement (CEM I) on the South African cement industry using the life cycle impact assessment (LCIA), based on the Recipe 2016 v 1.04 midpoint method. The study was conducted using data modeled after the South African cement plant, considered a cradle-to-gate system boundary, starting from the extraction of the raw material to the cement production process that produces cement as the main product. The data were obtained from the Ecoinvent database v3.7.1, integrated with SimaPro 9.1.1. software, used to assess the impact categories. For simplicity, the study merged the entire production process into five processes, i.e., raw materials usage, fuel consumption, clinker production, transportation and electricity. The impact categories of the five production stages were assessed using the LCA methodology. The impact categories investigated were classified into three categories: atmospheric, resource depletion and toxicity categories. According to the results, clinker production and electricity usage stages contribute the most to atmospheric impact (global warming, which causes climatic change due to high CO2 emissions), followed by raw materials and fuel consumption, contributing to the toxicity and resource depletion impact category. These stages contribute more than 76% of CO2 eq. and 93% of CFC-11 eq. In the midpoint method, CO2 is the most significant pollutant released. Therefore, replacing fossil fuels with alternative fuels can reduce fossil fuel use and the atmospheric impact of cement kilns.